2018
DOI: 10.1021/jacs.8b04742
|View full text |Cite
|
Sign up to set email alerts
|

Overriding Traditional Electronic Effects in Biocatalytic Baeyer–Villiger Reactions by Directed Evolution

Abstract: Controlling the regioselectivity of Baeyer-Villiger (BV) reactions remains an ongoing issue in organic chemistry, be it by synthetic catalysts or enzymes of the type Baeyer-Villiger monooxygenases (BVMOs). Herein, we address the challenging problem of switching normal to abnormal BVMO regioselectivity by directed evolution using three linear ketones as substrates, which are not structurally biased toward abnormal reactivity. Upon applying iterative saturation mutagenesis at sites lining the binding pocket of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 73 publications
4
62
0
Order By: Relevance
“…Mutations to the bulkier amino acids either significantly improved the regioselectivity for 'normal' lactone production from 2-methylcyclohexanone or allowed access to more of the 'abnormal' lactone from 2-methylcyclopentanone. This was similarly observed in directed evolution studies by Reetz and co-workers [33], where W492Y in TmCHMO did result in reduced activity, but at the gain of significantly improved regioselectivity for abnormal lactone products.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Mutations to the bulkier amino acids either significantly improved the regioselectivity for 'normal' lactone production from 2-methylcyclohexanone or allowed access to more of the 'abnormal' lactone from 2-methylcyclopentanone. This was similarly observed in directed evolution studies by Reetz and co-workers [33], where W492Y in TmCHMO did result in reduced activity, but at the gain of significantly improved regioselectivity for abnormal lactone products.…”
Section: Discussionsupporting
confidence: 71%
“…Interestingly, directed evolution studies with TmCHMO targeting the same amino acids in iterative saturation mutagenesis (ISM), found no hits with W492 in the reversal of enantioselectivity during the desymmetrization of the prochiral ketone 4-methylcyclohexanone [32], but W492Y/F mutations did significantly change the regioselelctiviey with 1-phenyl-2-propanone (phenylacetone) and 1-phenyl-2-butanone [33]. In silico analysis through substrate docking, molecular dynamics (MD) and quantum mechanical (QM/MM) simulations with density function theory (DFT) of the Criegee intermediate, however, do show the corresponding Trp in related BVMOs to contact the substrate or intermediate, rationalizing its involvement in changes in selectivity/specificity [30,[33][34][35]. In PAMO, the same changes in regioselectivity observed with W501A was also observed in Y502A, of which the side chain would not directly contact the substrate or reaction intermediates [28].…”
Section: Discussionmentioning
confidence: 99%
“…There are also Baeyer-Villiger-like oxidations of plant metabolites with unknown biosynthetic routes, such as the degradation of (+)-camphor in Salvia officinalis (sage; Croteau et al, 1984). The BVMOs have been used in numerous chemo-enzymatic applications, and their selectivity has also been successfully engineered (van Beek et al, 2012;Li et al, 2018a;Woo et al, 2018).…”
Section: Flavin Monooxygenasesmentioning
confidence: 99%
“…[24] According to the prevailing mechanism of the BV,the Criegee intermediate (CI)f avors the migration of the group that can best stabilize the partial positive charge. [25] Therefore,t he migrating atom should be C4, and not C2 from the carbonyl group (Scheme 4). Computational analysis at the wB97XD/6-311 + G(d,p) level of theory [26] revealed the existence of two stable Criegee intermediate conformers (CI1 and CI2)prone to form N-carboxyanhydride intermediates.B ecause of the presence of an intramolecular hydrogen bond (with an energy E(2) = 2.24 kcal mol À1 ), Criegee intermediate CI1 (in which the C2-C3 bond and OÀOb ond are antiperiplanar) is 4.36 kcal mol À1 more stable than CI2.F rom the optimization and the characterization of the TS1 and TS2 transition state structures for the reactions CI1!F and CI2!E,respectively, we found that the former transformation occurs at much lower energetic cost (DG°(TS1) = 20.22 kcal mol À1 )t han the latter (DG°(TS2) = 28.35 kcal mol À1 ).…”
Section: Angewandte Chemiementioning
confidence: 99%